Early initiation of intravenous cyclophosphamide and one‐year outcome in super‐refractory cryptogenic‐new onset refractory status epilepticus - Yasufumi Yorichika; Shuichiro Neshige; Hideaki Sakahara; Narumi Ono; Megumi Nonaka; Yuichiro Tagane; Tomoaki Watanabe; Keisuke Tachiyama; Haruka Ishibashi; Masahiro Nakamori; Takeo Shishido; Shiro Aoki; et al. (Epilepsia Open)
Abstract To explore the potential efficacy of early initiation of intravenous cyclophosphamide (IVCPA), we reviewed consecutive four cases of super‐refractory cryptogenic‐new onset refractory status epilepticus (C‐NORSE) between 2015 and 2023. We compared functional outcomes at 3 months and 1 year after the onset between patients who received IVCPA within 20 days (early‐treated) and those who received it later (late‐treated). All patients (median age: 43 years) had a prodromal fever. Brain MRI revealed symmetrically increased FLAIR signals in the medial temporal lobes of all patients. Despite initiating antiseizure medications (ASMs) and first‐line immunotherapy (intravenous‐methylprednisolone and immunoglobulins) within a median of 3 days from onset, SE persisted >5 days. The diagnosis of C‐NORSE was suggested based on a high C‐NORSE score (6/6). Thus, all patients received IVCPA a median of 15.5 days after seizure onset (three within 20 days and one at 31 days). One of the three early‐treated patients also received tocilizumab. Early‐treated patients exhibited shorter sedation periods (median 29 vs. 75 days) and better 1 year functional status (mRS 1–2 vs. mRS 4) compared to the late‐treated patient. Early initiation of IVCPA and/or tocilizumab, along with ASMs, may contribute to a better one‐year functional status in super‐refractory C‐NORSE patients. Plain Language Summary This study demonstrates the potential efficacy of early administration of intravenous cyclophosphamide on one‐year functional status in patients with super‐refractory cryptogenic‐new onset refractory status epilepticus. “Early‐treated patients” who received it within 20 days of seizure onset achieved a good one‐year functional status. The “late‐treated patient” (Case 4) who received it later did not achieve a good functional status. Early initiation of cyclophosphamide, along with antiseizure medications, may contribute to a better one‐year functional status in this population.